Razvijanje sposobnosti privzemanja perspektive kot eden izmed strukturnih elementov recepcijske sposobnosti - Kordigel Aberšek, Metka (Otrok in knjiga, 1999)
Receptive ability to perceive literary characters, their roles in the literary world and their function within the frame of a writer's intention of communication is strongly linked with child'a ability to adopt the perspective. It is the ability to image how things are seen by others, how/what they feel in a situation and conclude how they would behave or react. This is actually the adoption of the perspective of space, as well as social and emotional, the essential ability to understand the leading motivation of literary characters. Research about the development of a child's ability to adopt visual-spacious, emotional and informative perspectives was already carried out by Jean Piage in 1947. His experiment with hills is linked with the majority of the following contemporary studies studying this ability. The first four-levelled model of the development in a receptive situation was created by E. Andriga. She united Piage's scale of perceiving local perspectives and Selman's scale of developing the adoption of social perspectives when judging moral questions. Her research has shown that this development in a receptive situation goes on analogically with adopting the perspectives when solving local and socially moral questions from a total self-centredness on the first level to the fourth level. On the first level a child cannot imagine anyone seeing things differently than himself, while on the fourth, a reader notices a pattern of the internal literary perspectives from the literary historical perspective, literary theoretical perspective, the perspective of wider generic reality or the perspective of the author's intention of communication. The article compares the model and dynamic of the development of perceiving a perception with the curriculum for the nine-year primary school. It finds out that the creators of the curriculum, when defining the processed goals of single triennium, considered the dynamic of this receptive development
Keywords: mladinska književnost; young adult literature; literarna recepcija; child; otroci; otroška psihologija